2023
DOI: 10.1021/acssensors.2c02325
|View full text |Cite
|
Sign up to set email alerts
|

Vending-Machine-Style Skin Excretion Sensing

Abstract: Skin metabolites show huge potential for use in clinical diagnostics. However, skin sampling and analysis workflows are tedious and time-consuming. Here, we demonstrate a vending-machine-style skin excretion sensing platform based on hydrogel-assisted sampling of skin metabolites. In this sensing platform, a sampling probe with hydrogel is held by a robotic arm. The robotic arm manoeuvres the probe to press it onto the forearm of a human subject. Due to the highly hydrophilic nature of the hydrogel, water-solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In recent times, biocompatible agarose hydrogel is being utilized for manual sampling of human sweat and skin excretions. , However, it should be noted that although manual sample collection from human skin using hydrogels is simple, the desorption or re-extraction of analytes from the hydrogels and its subsequent detection require skill and expertise. In order to address this limitation, Yu et al developed a vending-machine-style skin excretion sensing platform, which serves to automate the sampling and analysis of human sweat and skin excretion . In this automatic sensing platform, the robotic arm picks up a hydrogel probe and collects the sample from the forearm (Figure -III-A).…”
Section: Different Types Of Sensing Systems With Elements Of Automationmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent times, biocompatible agarose hydrogel is being utilized for manual sampling of human sweat and skin excretions. , However, it should be noted that although manual sample collection from human skin using hydrogels is simple, the desorption or re-extraction of analytes from the hydrogels and its subsequent detection require skill and expertise. In order to address this limitation, Yu et al developed a vending-machine-style skin excretion sensing platform, which serves to automate the sampling and analysis of human sweat and skin excretion . In this automatic sensing platform, the robotic arm picks up a hydrogel probe and collects the sample from the forearm (Figure -III-A).…”
Section: Different Types Of Sensing Systems With Elements Of Automationmentioning
confidence: 99%
“…(III-B) Illustration of OPSI working principle. Reprinted with permission from ref ( 116 ). Copyright 2023 American Chemical Society.…”
Section: Different Types Of Sensing Systems With Elements Of Automationmentioning
confidence: 99%
“…Hand-held probes were also applied to detect pesticide residues on solid surfaces of fruits and vegetables, in different detection modes (ambient MS, biochemiluminescence). The efficacy of employing a hand-held aspirating probe for the sampling and transfer of concentrated VOCs to an ion-mobility spectrometry analyzer has been demonstrated in previous studies. , Another study demonstrated a vending-machine-style device that employs a robotic arm to sample analytes from the skin using hydrogel probes . A robotized probe was also coupled with MS for chemical mapping of VOCs in solid specimens …”
Section: Introductionmentioning
confidence: 97%
“…32,33 Another study demonstrated a vending-machine-style device that employs a robotic arm to sample analytes from the skin using hydrogel probes. 34 A robotized probe was also coupled with MS for chemical mapping of VOCs in solid specimens. 35 There is no universally accepted standard technique for analyzing VOCs from the skin's surface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…From the manufacturing tools used on the factory floor, to the inventory control devices used in commercial warehouses, even to the vacuum cleaners used in our homes, robots are deeply embedded in our daily lives. Modern analytical and clinical laboratories are critically dependent on robotic instrumentation for high-throughput analyses, and readers of ACS Sensors have begun to see how integration of the wide range of chemical and biological sensors into robots will massively expand the capabilities of these systems. As miniaturization and nanotechnological tools have evolved, the shrinking of these robots and their sensory systems to the nanoscale has brought its own set of promises and challenges.…”
mentioning
confidence: 99%